Sinopsis del género Gibsoniothamnus (Schlegeliaceae) en Costa Rica, con una nueva especie - Morales, J. Francisco (2016)
Gibsoniothamnus ficticius (Schlegeliaceae), a new species from Costa Rica, is described and illustrated, including notes on the relationships with related taxa. A brief synopsis for the genus in Costa Rica is provided, with a key for all the species.